The RNA N6‐methyladenosine demethylase ALKBH9B modulates ABA responses in Arabidopsis. Issue 12 (22nd November 2022) - Tang, Jun; Yang, Junbo; Lu, Qiang; Tang, Qian; Chen, Shuyan; Jia, Guifang
Abstract: The mRNA modification N 6 ‐methyladenosine (m 6 A) plays vital roles in plant development and biotic and abiotic stress responses. The RNA m 6 A demethylase ALKBH9B can remove m 6 A in alfalfa mosaic virus RNA and plays roles in alfalfa mosaic virus infection in Arabidopsis . However, it is unknown whether ALKBH9B also exhibits demethylation activity and has a biological role in endogenous plant mRNA. We demonstrated here that mRNA m 6 A modification is induced by the phytohormone abscisic acid (ABA) and that ALKBH9B has m 6 A demethylation activity on endogenous mRNA. Knocking out ALKBH9B led to hypersensitivity to ABA treatment during seed germination and early seedling development. We further showed that ALKBH9B removes the m 6 A modification in the ABA INSENSITIVE 1 ( ABI1 ) and BRI1‐EMS‐SUPPRESSOR 1 ( BES1 ) transcripts following ABA treatment, affecting the stability of these mRNAs. Furthermore, we determined that ALKBH9B acts genetically upstream of the transcription factors ABI3 and ABI5, and its regulatory function in ABA responses depended on ABI3 and ABI5. Our findings reveal the important roles of the m 6 A modification in ABA responses and highlight the role of ALKBH9B‐mediated m 6 A demethylation in regulating ABA responses post‐transcriptionally. Abstract : The RNA m 6 A demethylase ALKBH9B removes m 6 A from the ABSCISIC ACID (ABA) INSENSITIVE 1 ( ABI1 ) and BRI1‐EMS‐SUPPRESSOR 1 ( BES1 ) transcripts, thus stabilizing them and leading to the inhibition of ABI3 and ABI5 by ABI1 and BES1 proteins, promoting seed germination and early seedling development under ABA treatment.